Pencegahan Stunting Melalui Pelatihan Pemberian MP-ASI pada Ibu Bayi 6-24 Bulan di Desa Sungai Rasau Kecamatan Singkawang Utara - Tilawaty Aprina; Sofia Afritasari (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
The golden period in the first two years of a child's life can be achieved optimally if supported by proper nutritional intake from birth. Breast milk (ASI) as the only nutrition for babies up to six months of age is considered to play a very important role in growth and development, so that recommendations from the government, even WHO policies on this matter have been established and published throughout the world. The purpose of this study was to increase public knowledge about stunting in mothers of babies aged 6-24 months. The Community Service Method was carried out by means of counseling and practicing making MP-ASI. The results of community service showed that the implementation of MP-ASI training had increased awareness of the importance of MP-ASI to prevent stunting and support optimal child growth. The conclusion of the PKM activity was that on average participants were able to understand the material and practice how to process MP-ASI properly.